ANALISIS RELEVANSI MATA KULIAH DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN DENGAN DUNIA KERJA PARA LULUSAN - Maria Magdalena; Yuyun Estriyanto; Towip Towip (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
Current technological developments are called the industrial era 4.0 and society 5.0. Currently, education in Indonesia is experiencing an increase in the quality of higher education, namely with the issuance of the Independent Learning Campus policy which was launched by the Ministry of Education and Culture in 2020. In designing the 2021 Curriculum Study Program PTM FKIP UNS has a relationship with the needs of teacher competence, the curriculum applied in SMK, and the need for expertise competence in the industrial world. In this study, researchers will examine using a tracer study method for graduates of Mechanical Engineering Education UNS and the relevance of Mechanical Engineering Education courses at Sebelas Maret University Surakarta, especially according to alumni who graduated in 2017, 2018, 2019, and 2020. Research objectives This is